A Problem-Based Learning Electrochemistry Course for Undergraduate Students to Develop Complex Thinking - Aurora Ramos-Mejía; Kira Padilla (Education Sciences)
This paper presents a Problem-Based Learning (PBL) electrochemistry course contextualized within a real-world problem of wastewater treatment, designed to enhance students’ subject matter knowledge. The sample was a group of chemistry and chemical engineering undergraduate students who were taking an electrochemical course. The research outlines various activities and analyzes five cases of team learning outcomes using Atlas.ti(TM) 22 software. The analysis identifies and describes eight categories of scientific knowledge and practices derived from student reports. The results are represented using a Sankey diagram to show the complexity of students’ thinking after solving their problem. The findings indicate significant progress in students’ conceptual understanding of electrochemistry, the development of complex thinking, and the recognition of its relevance in solving everyday problems.